Use of N-LIST programme and the role of college librarians : a survey - Annu George; Mini G Pillai and Aparna P R
N-LIST- “National Library and Information Services Infrastructure for Scholarly Content”, jointly executed by UGC-INFONET Digital library Consortium, INFLIBNET Centre and INDEST-AICTE Consortium, IIT Delhi launched in 2010, aims at providing access to selected e-resources to students and teachers of affiliated colleges at affordable cost. The study aims at ascertaining the awareness of N-LIST programme among science and social science teachers of selected colleges, understand the usage pattern and preferences, level of satisfaction, the need for orientation programmes and the various suggestions put forward by the users. The questionnaire method was used for the study. Questionnaires were distributed to science and social science faculty members of five colleges. Most of the respondents were aware of N-LIST and majority of them came to know about N-LIST from their college librarian. It is found that teachers above the age of 45 years access N-LIST more than teachers of other age groups. Those in science subjects access N-LIST more. The teachers access N-LIST for preparing articles, teaching, preparing presentations for projects etc. Though they find N-LIST very useful, they face certain problems such as slow Internet connectivity and lack of infrastructure in colleges and limited resources available in N- LIST. A few of the respondents have suggested that more resources such as Science Direct may be included in N-LIST. It is hoped that programme will be accessible to more colleges with a wider coverage in future.